Ecological patterns of phytoplankton assemblages in Lake Garda: seasonal, spatial and historical features - Nico SALMASO (Journal of Limnology, 2002)
The development of phytoplankton assemblages in the two main basins of the deep (Zmax=350 m) and large (49 km3) subalpine Lake Garda (Northern Italy) was investigated through monthly samplings from 1998 to 2000. The algal development was strongly typified by the alternation, from spring to autumn, of Fragilaria crotonensis and Mougeotia sp. and by the increasing importance of filaments of the complex Planktothrix rubescens/agardhii in summer and autumn. These three “master species” are characterised by higher biovolumes and/or more regular and wide annual development in comparison to the other dominant taxa. The simultaneous application of ordination (NMDS-Non metric Multi Dimensional Scaling) and cluster analysis techniques revealed an ordered and coherent temporal succession of phytoplankton assemblages in the two main basins of the lake. These temporal and spatial regularities arise from the high inertia and resilience against perturbations that characterise the deep and large lakes, and contrast sharply with the less ordered or chaotic and unpredictable seasonal assemblages that may be found in small and shallow lakes. It is stressed that, owing to the use of different methodologies, the modifications of the phytoplankton assemblages in the last fifty years must be interpreted with particular caution. The only demonstrable differences seem to indicate that, with the speeding up of eutrophication processes in the 1960s and 1970s, detectable populations of Planktothrix and irregular increases of Conjugatophyceae (Mougeotia sp., Closterium aciculare) were established. During and after the 1980s, the increase of phosphorus concentrations in the lake and the progression towards more mesotrophic conditions was accompanied by the appearance of further substantial populations of cyanobacteria (Planktolyngbya limnetica, Anabaena lemmermannii). In contrast with these signs of alteration, Fragilaria crotonensis, Asterionella formosa, Ceratium hirundinella and Dinobryon spp. were among the most abundant taxa from the 1950s to the present time. These modifications are largely consistent with the changes observed during the 1990s in consequence of the different extent of the deep vertical mixing. During complete overturn, with the maximum spring replenishment of nutrients in the euphotic layers, a greater development of Mougeotia sp. and Oscillatoriales was observed. The historical trend and the ecological results allowed elucidation of the trophic characteristics of many important species developing in Lake Garda and, in general, in the deep subalpine lakes.